A preliminary comparison of using handheld devices in promoting the healthcare performance within a radiology department in terms of diagnostic accuracy and workflow efficiency. (1st January 2014) - Alamoudi, Abdullah O.; Haque, Syed; Srinivasan, Shankar; Mital, Dinesh P.
A preliminary research was conducted to compare the merits of using smartphones, iPad, and other tablet handheld devices with traditional systems in enhancing performance and workflow of radiology department. Review of work done on the topic was used as the secondary research method. There were not many works directly related to the topic. Hence, other related works were also reviewed. Nevertheless, handheld devices have many applications in telemedicine. In radiology, it is useful to transmit data and images to healthcare professionals for information, diagnosis and consultation. Image quality, screen size, resolution, transmission and response times are important in this aspect. In fact, different devices could differ in these and other technical aspects. These characteristics determine the relative usability of any handheld device. Although investment cost is high, patients receive healthcare at lower cost. Low cost community healthcare is also possible. Workflow efficiency from imaging procedure to diagnostic stage and finally to treatment phase is increased and performance of radiology professionals and the department are enhanced when handheld devices are used.